Revolutionizing Academic Writing: A Deep Dive into Hybrid Project-Based Learning - Rochmahwati, Pryla (Perkumpulan Dosen dan Pengajar Bahasa Inggris Se-Indonesia (ELITE Association Indonesia), 2024)
This study examines a novel Hybrid Project-Based Learning model in academic writing courses, presenting a revolutionary educational approach. A comprehensive case study was conducted in the English Department of IAIN Ponorogo, East Java, Indonesia. The study employed a robust qualitative research methodology and collected valuable information from data sources such as observations, interviews, and reflection. The investigation cantered on 85 fourth-semester students and three academic lecturers to establish a contextualized framework for comprehending the intricacies of implementing Hybrid PBL. The study utilized Thematic Analysis and QDA Miner software for data analysis. The study showed that the Hybrid-PBL academic writing approach begins by developing fundamental skills encompassing reading, note-taking, paraphrasing, and utilizing technology resources. The method proceeded with a project-based learning phase involving authentic writing problems, collaborative tasks, and a thorough process writing approach. Moreover, students offered significant insights emphasizing two primary themes: challenging yet rewarding and promoting a sense of value and approval. Keywords: academic writing; hybrid learning; project-based learning